Comparative evaluation of the subclinical coccidia population associated with enteric lesions in broiler - Gamboa González, Nidia; Duarte Rodríguez, Luz Zoraya; Cotamos López, Leonardo (Spei Domus, 2011)
We assessed the coccidia population in the feces of clinically healthy birds to determine the damage these parasites cause on intestinal integrity and their effect on zootechnical performance. The comparative evaluation of the population of subclinical coccidia made by the Universidad Cooperativa de Colombia, Bucaramanga branch, in 2010 used two groups. Group A consisted of 18.000 Ross breed females, group B consisted of 18.000 Cobb breed males, all between 1 and 42 days old. The birds were given an anticoccidial composite made from Narasin and Nicarbazin during the first three weeks of life and then only Nicarbazin during the remaining three weeks. The variables we evaluated weekly were: quantity of oocysts per gram of feces (using the McMaster method), zootechnical performance, and degrees of macroscopic and microscopic injury at 21, 28, and 35 days of age. We detected a count of oocysts per gram of feces from day 21 in group A and from day 28 in group B. The maximum count occurred around 28 and 35 days of age respectively. The areas with the highest degree of intestinal injury were: in group A, the duodenum, with mild to severe enteritis; and, in group B, the cecum with mild to severe typhlitis. Injury degrees observed macroscopically where different from those found microscopically, except for those associated with degree 1 injury in the cecum on group A and the duodenum in group B. The results in zootechnical performance were below those expected according to the standards for group A, in group B however, they exceeded the expectations.